Cityscapes in Sound: Tracing Urban Perceptions in Pop Music’ Lyrics and Sentiments Across Decades - Manifesty, Odilia Renaningtyas (Journal of Urban Society's Arts, 2024)
This study examines the representation of urban environments in popular music, analyzing how songs within similar eras depict particular perceptions of cities. The methodology consists of two main stages: systematic song selection from the mid-20th century to the present based on explicit urban references, followed by detailed song analysis using Python-based Natural Language Processing to measure urban theme strength, Pearson correlation analyses, and thematic assessments with TF-IDF and NMF techniques. Findings reveal a shift from mid-20th century idealistic views of urban life to more complex and nuanced representations reflecting contemporary social and economic realities. This evolution underscores pop music’s role as a mirror of urban experiences, capturing the vibrancy, challenges, and contradictions of city life. Limitation of the study includes the reliance on popularity metrics, as these may not fully capture a song’s cultural significance due to demographic biases and the influence of streaming algorithms. Nonetheless, this research contributes to urban studies and musicology by highlighting the intricate relationship between cultural expressions and urban perceptions. It suggests that utilizing pop songs as a methodological tool offers a novel way of understanding urban perception, providing an alternative to traditional studies that primarily focus on individual experiences. Penelitian ini mengkaji representasi lingkungan perkotaan dalam musik populer, menganalisis bagaimana lagu-lagu dalam era yang serupa menggambarkan persepsi tertentu tentang kota. Metodologi yang digunakan terdiri dari dua tahap: pemilihan lagu sistematis dari pertengahan abad ke-20 hingga saat ini berdasarkan referensi perkotaan yang eksplisit, diikuti dengan analisis lagu terperinci menggunakan Pemrosesan Bahasa Alami berbasis Python untuk mengukur kekuatan tema perkotaan, analisis korelasi Pearson, dan penilaian tematik dengan teknik TF-IDF dan NMF. Temuan mengungkapkan pergeseran dari pandangan idealistik kehidupan perkotaan di pertengahan abad ke-20 menjadi representasi yang lebih kompleks, mencerminkan realitas sosial dan ekonomi kontemporer. Evolusi ini menegaskan peran musik pop sebagai cermin pengalaman perkotaan, menangkap kehidupan kota yang penuh semangat, tantangan, dan kontradiksi. Keterbatasan studi ini termasuk ketergantungan pada metrik popularitas, karena ini mungkin tidak sepenuhnya menangkap signifikansi budaya sebuah lagu karena bias demografis dan pengaruh algoritma streaming. Namun demikian, penelitian ini memberikan kontribusi kepada studi perkotaan dan musikologi dengan menyoroti hubungan rumit antara ekspresi budaya dan persepsi perkotaan, membentuk bagaimana kehidupan kota dialami dan dipahami. Makalah ini menyarankan bahwa menggunakan lagu pop sebagai alat metodologis menawarkan cara baru untuk memahami persepsi perkotaan, menyediakan alternatif untuk studi tradisional yang kebanyakan berfokus pada pengalaman individu.